Probabilistic evaluation of seismic performance of 3 story 3D one and two way steel moment frame structures. - Tagawa, Hiroyuki (Earthquake engineering & structural dynamics.)
This paper presents the results of a probabilistic evaluation of the seismic performance of 3D steel moment frame structures. Two types of framing system are considered : one-way frames typical of construction in the United States and two way frames typical of construction in Japan. For each framing system, four types of beam column connections are considered : pre-Northridge welded flange bolted web, post Northridge welded flange welded web, reduced beam section, and bolted flange plate connections. A suite of earthquake ground motions is used to compute the annual probability of exceedence (APE) for a series of drift demand levels and for member plastic rotation capacity. Results are compared for the different framing systems and connection detaisl. It is found that the two way frames, which have a larger initial stiffness and strength than the one way frames for the same beam and column volumes, have a smaller APE for small drift demands for which members exhibit no or minimal yielding but have a larger APE for large drift demands for which members exhibit large plastic rotations. However, the one way frames, which typically comprise a few seismic frames with large sized members that have relatively small rotation capacities, may have a larger APE for member failure. The probabilistic approach presented in this study may be used to determine the most appropriate frame configuration to meet an owner's performance objectives.